Elephantis, a new genus for Caridina natalensis Bouvier, 1925 from eastern rivers of Madagascar - Castelin, Magalie; Marquet, Gerard; Klotz, Werner (Zootaxa, 2013)
Elephantis, new genus, is established for Caridina natalensis Bouvier, 1925 hitherto known only from South Africa with one male specimen. Recently, three surveys by electric fishing (2004, 2008 and 2010) of some eastern rivers from Madagascar have permitted to discover numerous specimens of this species. Caridina natalensis is different from all other known species of Caridina by its remarkably broad endopod of the male first pleopod, a long clubbed appendix masculina on the male second pleopod reaching beyond distal end of endopod and strong third pereiopods. Therefore a new genus name is proposed for this species. In addition to detailed description of diagnostic morphological characters, molecular sequences obtained from mitochondrial 16S gene are provided for six specimens of this species. These DNA sequences are integrated to the 16S molecular phylogeny of atyid freshwater shrimps recently published by von Rintelen et al. (2012). Elephantis natalensis comb. nov. sequences formed a divergent group supported in maximum likelihood analysis. The availability of DNA samples could be used as reference and integrated in further phylogenetic studies on atyid freshwater shrimps.